Diet development and rearing of the Cape fly, Ceratitis quilicii (Diptera: Tephritidae) - Basson, Michael Nicolaas Smuts (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.